2011
DOI: 10.1089/pop.2010.0020
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Care for Veterans with Chronic Diseases: Performance on Quality Indicators, Medication Use and Adherence, and Health Care Utilization

Abstract: This study was conducted to assess and benchmark the quality of care,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 17 publications
(24 reference statements)
0
19
2
Order By: Relevance
“…Although several medications are available to prevent and control COPD symptoms and exacerbations, a large proportion of COPD patients remain untreated 16. Furthermore, medication adherence levels for mCOPD medications have been found to be suboptimal and lower than the levels typically observed for treatments for other conditions 58. One of the reasons for suboptimal adherence to COPD medications may be due to the symptomatic nature of the disease leading to adjustment of medication use depending on how the patients feel on any particular day 9.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although several medications are available to prevent and control COPD symptoms and exacerbations, a large proportion of COPD patients remain untreated 16. Furthermore, medication adherence levels for mCOPD medications have been found to be suboptimal and lower than the levels typically observed for treatments for other conditions 58. One of the reasons for suboptimal adherence to COPD medications may be due to the symptomatic nature of the disease leading to adjustment of medication use depending on how the patients feel on any particular day 9.…”
Section: Discussionmentioning
confidence: 99%
“…Medication adherence levels for COPD medications have been found to be well below the levels typically observed for treatments for other conditions 58. For example, in a 2011 study of US military veterans, proportion of patients adherent to COPD treatments, defined as proportion of days covered (PDC) ≥0.80, was reported to be approximately 30% versus 40%–63% for coronary artery diseases, diabetes, heart failure, and hyperlipidemia treatments 8…”
Section: Introductionmentioning
confidence: 99%
“…However, unlike other chronic diseases, medication adherence in COPD has found to be quite low [2][3][4]. For instance, in a previous study Neugaard et al [5] showed that among US military veterans, COPD medication adherence was 30%, whereas for coronary artery diseases, diabetes, heart failure, and hyperlipidemia treatments, the adherence was 40%-63%. Multiple factors, including patient beliefs, knowledge, and attitude, regarding to both illness and therapy have shown to be equally important in medication adherence as with social, demographic, and clinical factors in patients with COPD [6].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, 8.76 million veterans 65 years or older are enrolled in the VHA health care system, with 75% of those having 1 or more chronic disease process. [11][12][13][14][15][16] Veterans 85 years or older increased by 190% between 2000 and 2010, whereas the general US population of the same age rose by only 44%. 17 Many of the symptoms associated with chronic disease processes leave individuals physically and cognitively debilitated, making routine care more difficult to obtain.…”
mentioning
confidence: 99%